Does net energy cost of swimming affect time to exhaustion at the individual's maximal oxygen consumption velocity? - Fernandes, R. J.; Billat, V. L.; Cruz, A. C.; Colaco, P. J.; Cardoso, C. S.; Vilas-Boas, J. P. (The Journal of Sports Medicine and Physical Fitness, 2006)
Aim: The purpose of the present study was to examine the relationship between time limit at the minimum velocity that elicits the individual's maximal oxygen consumption (TLim-v V.O2max) and three swimming economy related parameters: the net energy cost corresponding to v V.O2max (Cv V.O2max), the slope of the regression line obtained from the energy expenditure (E.) and corresponding velocities during an incremental test (Cslope) and the ratio between the mean E. value and the velocity mean value of the incremental test (Cinc). Complementarily, we analysed the influence of Cv V.O2max, Cslope and Cinc on TLim-v V.O2max by swimming level. Methods: Thirty swimmers divided into 10 low-level (LLS) (4 male and 6 female) and 20 highly trained swimmers (HTS) (10 of each gender) performed an incremental test for v V.O2max assessment and an all-out TLim-v V.O2max test. Results: TLim-v V.O2max, v V.O2max, Cv V.O2max, Cslope and Cinc averaged, respectively, 313.8±63 s, 1.16±0.1 m . s-1, 13.2±1.9 J.kg-1.m-1, 28±3.2 J.kg-1.m-1 and 10.9±1.8 J.kg-1.m-1 in the LLS and 237.3±54.6 s, 1.4±0.1 m . s-1, 15.6±2.2 J.kg-1.m-1, 36.8±4.5 J.kg-1.m-1 and 13±2.3 J.kg-1.m-1 in the HTS. TLim-v V.O2max was inversely related to Cslope (r=-0.77, P<0.001), and to v V.O2max (r=-0.35, P=0.05), although no relationships with the Cv V.O2max and the Cinc were observed. Conclusions: The findings of this study confirmed exercise economy as an important factor for swimming performance. The data demonstrated that the swimmers with higher and v V.O2max performed shorter time in TLim-v V.O2max efforts.